The Adventures of a Bribri Around the World Looking for the Identity of his People. Interview with Alí García Segura - Guevara Berger, Marcos (2021)
Interview with Mr. Alí García Segura, an academic from the University of Costa Rica dedicated to the study of indigenous languages. It narrates aspects of his personal history that support his work as a researcher, his search for representative objects for the Bribri culture such as the tsáwö and the seat of Sibö̀ that led him to visit important museums abroad and, also, to inquire about the role of foreign researchers who, in the 19th and 20th centuries, visited Talamanca and were involved with the extraction of these pieces. It ends with a reflection about the identity of the indigenous community and the importance of the participation of its members in institutions linked to the preservation of their heritage.